Effect of different types of damping winding structures on the no-load magnetic field of a tubular hydro‑generator - Zheng, Qiao-Yun; Fan, Zhen-Nan; Zhou, Zhi-Ting (Archives of Electrical Engineering (Online), 2025)
The no-load magnetic field of a hydro-generator significantly impacts the quality of its no-load voltage waveform and the grid power quality and power system stability. As a vital element for ensuring the safe and steady operation of hydro-generators, the damping winding structure directly affects the state of the no-load magnetic field. Particularly, horizontal hydro-generators, such as tubular turbine units, feature confined and irregular internal spaces that lead to more intricate and intense distributions of the magnetic field. Therefore, to improve the quality of no-load voltage waveforms, grid power quality, and overall power system stability, it is essential to examine how variations in damping winding structure types affect the no-load magnetic field in these generators. This paper considers a specific 34-MW large tubular turbine generator as an example. A 2D transient electromagnetic field model was developed to investigate the effects of four damping winding structures—fully damped, semi-damped, isolated damping bar, and solid-steel pole—on the mag-nitude and distribution of the no-load magnetic field, the quality of the no-load volt-age waveforms, and the eddy-current losses within the damping system. The research directly supports the design and manufacturing processes of tubular hydro-genera-tors and ensures the safety and stability of generator and power system operations.